EFEKTIVITAS PEMBERDAYAAN MASYARAKAT HOME INDUSTRY SEKTOR PERIKANAN PASCA BENCANA TSUNAMI DI KOTA BANDA ACEH - Yulia Hastuti; Muchlisin Muchlisin; Indra Indra (Jurnal Manajemen Inovasi, 2017)
AbstractFishery processing business located in the coastal area of Banda Aceh city is one of the business sectors affected by tsunami disaster in 2004. Assistance to empowerment programs provided by the government as well as the role of financing institutions, especially in the development of small and medium enterprises still focus on capital with credit/loan facilities, as well as getting personal coaching and business development. This study is aimed to determine the effectiveness of community empowerment program assistance home industry to the success of fishery processing business after the tsunami in Banda Aceh. This type of research includes descriptive survey research with quantitative analysis. The data were collected through questionnaires, interviews, documentation and literature studies. The results of the research showed the implementation of home industry community empowerment program home industry post tsunami disaster based on input parameters, process and output quite effective. The effectiveness of each score is the Assistance of Fisheries Department (BDP) of 76.44%, Financing Institution Funding (BLP) 72.02%, and Assistance for Fisheries and Financing Institution (BDPLP) 71.73%. This indicates that the assistance of the program can increase the income and production of the business that impact on the existence of business potential of fishery business group. Keywords: Community Empowerment, Effectiveness,  Disaster, Home Industry